The Functional Response of Estuarine Fish Communities to Hydrologic Change in a Semi-Arid Ecosystem - Lisa A. Gonzalez; Antonietta Quigg (Fishes)
Functional assessment approaches were used to identify the responses of fish to environmental change in the San Antonio Bay System (Texas, USA). Using a 26-year coastal fisheries dataset (1993–2018), multivariate analyses revealed relationships between functional group abundance and freshwater inflows in the upper segments (Hynes Bay and Guadalupe Bay), but the patterns were decoupled from inflows in the lower bay segments (San Antonio Bay, Ayres Bay and Espiritu Santo Bay). In Hynes and Guadalupe Bays, freshwater migrant carnivores accounted for a significant fraction of the community irrespective of the gear, year or flow. Freshwater stragglers (omnivores and carnivores) were often present in the upper reaches of the bay. In the lower reaches, marine migrant omnivores were present during high and low flows in Espiritu Santos Bay, but only during low flows in Ayres Bay. Marine migrant carnivores were more important in gill nets irrespective of the flow conditions. The five most abundant fish were estuarine resident carnivores and omnivores, accounting for 53.5% of the community. Declines in the abundance of functional groups occurred during the 2011–2014 drought, with rebounds in 2015–2018. Functional methodologies provide insights into estuarine ecosystems and can serve as management tools to assess changes in fish assemblages.